Průbĕh a výsledky 34 tĕhotenství komplikovaných syndromem HELLP - Simetka, O; Michalec, I; Zewdiová, H; Kolárová, R; Procházková, J; Procházka, M (Ceska gynekologie, 2010)
OBJECTIVE: To analyze the course and delivery outcomes of pregnancies complicated by HELLP syndrom and compare them to previously published data. DESIGN: Retrospective cohort study. SUBJECT AND METHOD: We analyzed pregnancy outcomes of 34 pregnancies complicated by HELLP syndrom of women who delivered at our hospital between years 2004 and 2009. SETTING: Department of Obstetrics and Gynecology, University Hospital Ostrava. RESULTS: There were 34 pregnancies and deliveries complicated by HELLP syndrom between the years 2004 and 2009 (64 months). The average age of mothers was 28.5 years, the average gestational age at delivery time was 33 weeks and 4 days. Only 2 women delivered vaginaly, the other 32 delivered by cesarean section and the average weight of the newborn was 1930 g. There were 3 twin pregnacies. Twenty two (65%) patients had laboratory abnormalities in coagulation parameters but clinical signs of coagulation disorder were noted in 8 patients only (23.5%). Six patients recevied blood transfusions (18 units in total) and 9 patients received plasma transfusions (20 units in total). The average length of stay of mothers at intensive care unit was 3.2 days. There was no maternal mortality. One fetus was stillborn and 12 newborns (33.3%) had their early postnatal period complicated by severe morbidity. CONCLUSION: Early diagnosis and active management is a major factor for the prevention of severe forms of HELLP syndrom which still remains one of the most severe complications of pregnancy.
Keywords: Delivery, Obstetric; Infant, Newborn, Diseases; HELLP Syndrome; těhotenství; mladiství; výsledek těhotenství; Adult; mladý dospělý; poruchy v puerperiu; vedení porodu; Infant, Newborn; Young Adult; ženské pohlaví; novorozenec; Puerperal Disorders; Humans; Pregnancy; nemoci novorozenců; Pregnancy Outcome; dospělí; HELLP syndrom; Female; Adolescent; lidé